Autoclaved Fly-Ash Pellets as Replacement of Coarse Aggregate in Concrete Mixture - Ghosh, Biswaroop (AMC Indian Journal of Civil Engineering, 2018)
Coal, which is a very promising material for a growing country like India produces fly- ash which is creating a great threat to the environment. Fly-ash is mainly used for dumping or as a fine aggregate. The present study is aimed at developing a technique for producing an aggregate with fly-ash using autoclave and use it in the replacement of normal coarse aggregate. The properties of fly-ash were experimentally checked, whether it is of type-C or of type-F by chemical analysis of the fly-ash. Batches of fly-ash aggregates were manufactured using Autoclaved technique using disc pelletilizer. Based on the cursing value, water absorption, and impact value test results of their properties, fly-ash aggregates were selected. Using the fly-ash aggregates prepared from the Autoclaved technique, their properties were tested. These pellets will be light in weight having specific gravity less than that of gravel (2.67) and will have high impact value than that of gravel (20.12). At the same time, they will also address some of the environmental problems such as disposing the industrial waste which is being generated from thermal waste.